Use of GnRH to increase the precision of estrus and augment timed insemination in heifers treated with melengesterol acetate and PGF2 - Broweleit, B.; Huston, J.E.; Grum, D.E.; Day, M.L.; Johnson, Sandra K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We examined the potential of adding gonadotropin-releasing hormone (GnRH) to a synchrony system based on melengestrol acetate-prostaglandin F2(MGA-PGF2) to increase the precision of synchronized estrus and augment timed artificial insemination (AI). Yearling heifers were fed MGA daily for 14 days. Nineteen days after the last feeding of MGA, all heifers were given PGF2(day 0). Heifers receiving no further treatment served as the untreated controls. In the second treatment, heifers also received an injection of GnRH on day –7. Both groups of heifers were artificially inseminated 12 hours after detected estrus. Heifers in the third treatment received GnRH on day –7 and day 2 and were inseminated (timed AI) at the time of the second GnRH injection. In comparison to a MGA-PGF2 synchronization system, addition of GnRH on day –7 did not improve the synchrony of estrus. Adding two injections of GnRH (day –7 and day 2) facilitated timed AI. However, pregnancy rate for timed AI was lower than pregnancy rate for AI 12 hours after detection of estrus.
Keywords: Beef; AI; Estrus synchronization; Timed AI; GnRH; MGA; Heifers